Entrepreneurship in BRICS: Policy and Research to Support Entrepreneurs - La Rovere, Renata (Springer, 2015)
This book presents selected articles that discuss important issues related to entrepreneurship in Brazil, Russia, India and China as well as contributions from authors whose countries have a tradition on entrepreneurship support, such as Italy and the UK. The articles were presented and discussed in a conference on Entrepreneurship in Brazil in November 2013 organized by the Institute of Economics of the Federal University of Rio de Janeiro and IBMEC Business School. This book covers four essential themes: financing entrepreneurs, innovation environments, social entrepreneurship and e-entrepreneurship.